2016
DOI: 10.4103/1673-5374.169638
|View full text |Cite
|
Sign up to set email alerts
|

Influence of immobilization and sensory re-education on the sensory recovery after reconstruction of digital nerves with direct suture or muscle-in-vein conduits

Abstract: The influence of duration of immobilization and postoperative sensory re-education on the final outcome after reconstruction of digital nerves with direct suture or muscle-in-vein conduits was investigated. The final sensory outcome of 35 patients with 41 digital nerve injuries, who either underwent a direct suture (DS) or a nerve reconstruction with muscle-in-vein conduits (MVC), was assessed the earliest 12 months postoperatively using static and moving two-point discrimination as well as Semmes-Weinstein mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This finding can be attributed to the therapeutic effect of the standard exercise program (e.g., tendon and median nerve gliding), which agreed with Warran, 2001, who reported that standard physical therapy treatment was effective in treatment of for CTS symptoms [27]. The additional improvement in the group who received sensory re-learning may be attributed to improvement of hand sensibility as there is a direct correlation between motor and sensory conduction velocities of the median nerve and hand grip strength in women as reported by Abdel-Fattah et al, 2014 Improving sensibility threshold will improve motor function and overall functional outcome of the hand [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding can be attributed to the therapeutic effect of the standard exercise program (e.g., tendon and median nerve gliding), which agreed with Warran, 2001, who reported that standard physical therapy treatment was effective in treatment of for CTS symptoms [27]. The additional improvement in the group who received sensory re-learning may be attributed to improvement of hand sensibility as there is a direct correlation between motor and sensory conduction velocities of the median nerve and hand grip strength in women as reported by Abdel-Fattah et al, 2014 Improving sensibility threshold will improve motor function and overall functional outcome of the hand [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a systematic review by Manoli et al, 2016 reported limited evidence supporting the use of early and late sensory relearning modalities in the treatment of peripheral nerve lesions, also only mixed nerves were included in the analysis [26].…”
Section: Discussionmentioning
confidence: 99%